The interplay between autophagy and ROS in tumorigenesis - Kongara, Sameera; Karantza, Vassiliki (Frontiers in Oncology, 2012)
Reactive oxygen species (ROS) at physiological levels are important cell signaling molecules. However, aberrantly high ROS are intimately associated with disease and commonly observed in cancer. Mitochondria are primary sources of intracellular ROS, and their maintenance is essential to cellular health. Autophagy, an evolutionarily conserved process whereby cytoplasmic components are delivered to lysosomes for degradation, is responsible for mitochondrial turnover and removal of damaged mitochondria. Impaired autophagy is implicated in many pathological conditions, including neurological disorders, inflammatory bowel disease, diabetes, aging, and cancer. The first reports connecting autophagy to cancer showed that allelic loss of the essential autophagy gene BECLIN1 (BECN1) is prevalent in human breast, ovarian, and prostate cancers and that Becn1+/- mice develop mammary gland hyperplasias, lymphomas, lung and liver tumors. Subsequent studies demonstrated that Atg5-/- and Atg7-/- livers give rise to adenomas, Atg4C-/- mice are susceptible to chemical carcinogenesis, and Bif1-/- mice are prone to spontaneous tumors, indicating that autophagy defects promote tumorigenesis. Due to defective mitophagy, autophagy-deficient cells accumulate damaged mitochondria and deregulated ROS levels, which likely contribute to their tumor-initiating capacity. However, the role of autophagy in tumorigenesis is complex, as more recent work also revealed tumor dependence on autophagy: autophagy-competent mutant-Ras-expressing cells form tumors more efficiently than their autophagy-deficient counterparts; similarly, FIP200 deficiency suppresses PyMT-driven mammary tumorigenesis. These latter findings are attributed to the fact that tumors driven by powerful oncogenes have high metabolic demands catered to by autophagy. In this review, we discuss the relationship between ROS and autophagy and summarize our current knowledge on their functional interactions in tumorigenesis.